THE ROLE OF ARTIFICIAL INTELLIGENCE IN TRANSLATION (Ustozlar uchun, 2026)
The integration of artificial intelligence (AI) into translation processes has fundamentally transformed the field of translation studies and practice. This article examines the impact of AI technologies, including machine translation (MT), neural machine translation (NMT), and natural language processing (NLP), on the efficiency, accuracy, and scalability of translation workflows. While AI-driven systems offer rapid, large-scale translation capabilities, challenges persist in handling context, idiomatic expressions, and culturally nuanced content. The study further explores the complementary role of human translators in post-editing, quality assessment, and contextual interpretation, emphasizing the emergence of hybrid translation models that combine AI efficiency with human expertise. The findings highlight that AI is not a replacement for human translators but a transformative tool that reshapes their roles, enhances productivity, and expands the possibilities for multilingual communication in a globalized, digital environment.